Hyperbaric oxygenation in prevention of amputations of diabetic foot - Stefanović Zvezdan; Donfrid Branislav; Jovanović Tomislav; Zorić Zoran; Radojević-Popović Radmila; Zoranović Uroš (Vojnosanitetski Pregled)
Background/Aim. Diabetic foot is the term for the pathological changes on foot in patients with diabetes. It is caused by diabetic angiopathy, polyneuropathy and osteoarthropathy. The treatment is complex and long-term and often leads to the loss of the extremity. The appliance of hyperbaric oxygen therapy (HBOT) has a lot more important place in adjuvant treatment of this disease. The aim of this study was to determine the influence of HBOT on the wound healing in comparison with the conventional treatment, the possibility of shortening the time of the treatment in patients with diabetic foot. Methods. In a fiveyear period a retrospective-prospective multicentric study, involving 60 patients with diabetic foot divided into two groups, was performed. The first group (group A) consisted of 30 patients treated by combined therapy (with medications, surgical therapy and HBOT). All the patients were receiving HBOT in the Special Hospital for Hyperbaric Medicine, CHM Hollywell-Neopren in Belgrade. The control group (group B) also consisted of 30 patients treated with medications and surgical therapy, but without HBOT. Results. The demographic data, the types of diabetes, as well as the Wagner classification stage of diabetic ulcers and radiography scans of changes in bones were equal in both groups. The median healing time of the Wagner grade III ulcer in the group A was 37.36 days [mean ± standard deviation (SD) = 65.6 ± 45.8 days], and in the group B 99.78 days (mean ± SD = 134.8 ± 105.96 days) and it was statistically significant (p = 0.074). The median time of recovery in patients of the group A with the Wagner grade IV was 48.18 days (mean ± SD = 49.7 ± 33.8 days), and in the group B 85.05 days (mean ± SD = 86.7 ± 71.6 days) and that was statistically significant (p = 0.121). The foot amputations were performed in both groups in 3 (10%) patients. In the group A there were no high amputations, whereas in the group B there were 4 (13.33%) below-knee amputations and 4 (13.33%) above-knee amputations which was highly statistically significant (p < 0.0001). Conclusion. In this study, HBOT definitely showed positive adjuvant role in the treatment of diabetic foot. For the good treatment result it is essential the timely and successful surgical treatment of the ulcer and the use of bandage with the healing dressings. In case of the clear signs of local infection, the antibiotic therapy according to the antibiogram is necessary.